Explaining the Financial Distress Model Based on a Combined Framework of Accounting and Auditing Information: Examining and Comparing the Altman, Zmijewski, and Combined Models - Pourhosein Tahergourabi , Mohammad Reza; Barari Nokashti, Soghra; Khodadadi , Mohsen (Business, Marketing, and Finance Open, 2024)
The present study aims to explain the financial distress model based on a combined framework of accounting and auditing information by examining and comparing the Altman, Zmijewski, and combined models. This study is applied in nature, as its results can be used in decision-making processes. Since the data in this research were collected based on real historical information, it is classified as ex-post facto research. Regarding hypothesis inference, this study falls under the category of descriptive-correlational research, as regression and correlation techniques were employed to determine the relationships between variables. Therefore, in terms of reasoning, it belongs to the category of inductive research. Additionally, this study follows a positive theoretical approach, as conclusions are drawn by testing existing data. To achieve the research objective, data from 87 companies listed on the Tehran Stock Exchange between 2013 and 2022 were collected and analyzed using logistic regression based on panel data. The results indicate that the modified Altman and Zmijewski models, based on a combined framework of accounting and auditing information, demonstrate greater predictive power in forecasting corporate financial distress compared to the original Altman (Zmijewski) model. Furthermore, the findings reveal that incorporating a combined framework of accounting and auditing information into the original Altman (Zmijewski) model enhances the ability to predict financial distress in companies.